Implementation of Management Technologies for Innovative Development of the Region - Salamova Ayna (SHS Web of Conferences, 2021)
The transition of the Russian economy to an innovative path of development, the most complete and rational use of the economic, scientific, technical and intellectual potential of each region will largely depend on the effectiveness of management at the regional level. In this regard, there is a need to develop a methodology for the formation and implementation of management technologies for innovative development of the region. Management technologies are understood as technologies that help to reduce production costs in different sources of their occurrence, as well as are carried out through decision-making at the regional level. Management technologies for innovative development of territories should ensure the concentration of resources in priority areas and create conditions for interregional cooperation, business, public institutions within the framework of innovative development.